PENGARUH PERPUTARAN KAS DAN PERPUTARAN PIUTANG TERHADAP PROFITABILITAS(Studi Pada Perusahaan Sektor Property dan Real Estate yang Terdaftar di Bursa Efek Indonesia) - Audy Yohanes Leatemia; Annas Lalo (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2023)
The type of data in this research is quantitative data. The data source in this study is secondary data, in the form of financial report data (balance sheet and income statement) related to the variables in this study. The results of this study indicate that cash turnover has a significant negative effect on profitability. Meanwhile, accounts receivable turnover has a non-significant negative effect on profitability. The results of the study simultaneously show that cash turnover and accounts receivable turnover have a positive and significant effect of 12.9% on profitability and the remaining 87.1% are influenced by other variables not examined